Tanggung Jawab Negara Asal Virus Covid-19 Perspektif Hukum Islam dan Hukum Internasional - Nurjanah Nurjanah; Hifdhotul Munawaroh (Program studi Keagamaan Islam, 2021)
The spread of the Covid-19 virus has been very massive almost all over the world, Covid-19 is a real threat to humans and countries because it causes some global losses and damage. The perceived losses have led several countries to sue China to be responsible and immediately be tried in an international court. This research aims to know, understand, and analyze the regulatory responsibilities of countries in Islamic law and international law perspective and whether or not the country of origin of the Covid-19 outbreak is held accountable for a global Covid-19. This research is normative legal research with a statutory approach. The results of this study explain that China could be held accountable if it met certain characteristics of the Covid-19 case, but it is not easy for China to be held accountable for this Covid-19 case which almost in several countries in the world